Economic and distributional impacts of turning the value-added tax into a carbon tax - Miguel Angel Tovar Rea\~nos; Kelly C. De Bruin; David Meier; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2022)
We construct carbon footprints from households' expenditure and employ the EASI demand system to simulate the distributional and environmental effects of a introducing a 'green VAT' in Ireland. For our analysis, we combine expenditure data from the Irish Household Budget Survey with data on consumption-based emissions. We consider three scenarios: one with no recycling mechanism for additional tax revenue, one with a five per cent higher state transfers and one with an income tax cut. In all scenarios, the existing VAT system is replaced by a combination of a uniform base rate of four per cent and a strong carbon tax component. The policy leads to a reduction in emissions from households of roughly 6 per cent. We find that households' footprints are strongly driven by expenditure on energy and transport. Average emissions footprints are higher for high-expenditure quartiles. We also find that while the tax leads to welfare drops for all households, especially those at the lower end of the distribution of household expenditure, the combined carbon tax and transfer increase are protecting at least the lowest two deciles of the expenditure distribution from the adverse welfare effects. The income tax cut limits the reduction in working hours present in the other two scenarios. Both revenue recycle mechanisms weaken the reduction in emissions.
Keywords: D12; H23; Q58; 330